2006
DOI: 10.1016/j.jacc.2006.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Bone Marrow Stem Cell Mobilization Induced by Granulocyte Colony-Stimulating Factor After Subacute ST-Segment Elevation Myocardial Infarction Undergoing Late Revascularization

Abstract: Granulocyte colony-stimulating factor treatment after PCI in subacute STEMI is feasible and relatively safe. However, patients do not benefit from G-CSF when PCI is performed late. Granulocyte colony-stimulating factor results in improved myocardial perfusion of the infarcted area, which may reflect enhanced neovascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
129
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(135 citation statements)
references
References 25 publications
5
129
0
1
Order By: Relevance
“…However, a lot of conflicting results were reported about improvement in cardiac function. In 2006, three prospective, randomized, double-blinded, placebo-controlled trials in patients diagnosed with ST-segment elevation acute MI who had successful reperfusion by PCI were performed [28][29][30]. They used the same dose of G-CSF (10 μg/kg of body weight) for 5 or 6 consecutive days.…”
Section: Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a lot of conflicting results were reported about improvement in cardiac function. In 2006, three prospective, randomized, double-blinded, placebo-controlled trials in patients diagnosed with ST-segment elevation acute MI who had successful reperfusion by PCI were performed [28][29][30]. They used the same dose of G-CSF (10 μg/kg of body weight) for 5 or 6 consecutive days.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Primary or secondary end-points included cardiac function assessed by MRI, and the follow up varied from 3 to 6 months. All studies failed to show benefits of G-CSF treatment in LVEF either when PCI was done early (<12hs) [29,30] or late (mean of 31hs-2 to 107hs) [28]. At the end of 1 year of follow up G-CSF was still inefficacious in improving cardiac function [31].…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Of the safety trials, only one showed enhanced PI-LVF with G-CSF at 4 months [38]. REVIVAL-2 and GCSF-STEMI were designed as randomized, blinded trials powered to assess the effect of post-PCI G-CSF on PI-LVF [39,40]. Neither of these trials reported significant rates of restenosis with G-CSF, but neither trial demonstrated any changes in infarct size or PI-LVF 3-6 months following G-CSF administration.…”
Section: G-csf Mobilizationmentioning
confidence: 99%
“…However, other studies performed under similar conditions have found no functional improvement for intracoronary delivery [16,17] and no positive effect following transendocardial delivery [18]. Mobilization of BM stem cells either as a natural response to injury [19] or with granulocyte colony-stimulating factor [20] show functional improvements, albeit limited, which may be linked to improved perfusion of the infarcted area. Mobilized CD34 + cells have been shown to contribute to vasculogenesis and cardiomyogenesis in rats [21], and have also been shown to have greater efficacy than total mononuclear cells [22].…”
Section: Introductionmentioning
confidence: 99%